Plant-beneficial Bacillus, Pseudomonas, and Staphylococcus spp. from Kumaon Himalayas and their drought tolerance response - Sati, Diksha; Pande, Veni; Samant, Mukesh (Frontiers in Sustainable Food Systems, 2023)
Plant growth-promoting rhizobacteria (PGPR) have been shown to augment plant responses against drought and other abiotic stresses. In the present study, we isolated 27 bacteria from the rhizosphere of various plants cultivated in the Kumaon Himalayas., and to measure their abiotic stress tolerance, these 27 isolates were subjected to variations in pH, temperature, and drought. All 27 isolates were also screened for various plant growth-promoting traits. Among these, the four isolates RR1, ASC1, AFS3, and NG4 demonstrated various plant growth promotion activities including the synthesis of indole-3-acetic acid (IAA), siderophores, ammonia, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase production, and concomitantly high tolerance to abiotic stresses. Moreover, 16S rRNA sequencing of these four isolates validated their identities as Bacillus, Pseudomonas, and Staphylococcus sp. Finally, to assess the in-vivo drought tolerance potential of these four isolates, a pot-trial experiment was undertaken in wheat cultivar VL-892. The results demonstrated that inoculating wheat plants with these four PGPR isolates greatly improved plant growth under drought circumstances by increasing root and shoot length and both fresh and dry weight of root and shoot. This study endeavors to discover the biochemical and molecular diversity of cultivable PGPR in six remotely located districts of Uttarakhand. In conclusion, the drought-tolerant PGPR strains described in this study are plant-beneficial and can effectively mobilize nutrients under drought conditions. Consequently, they could be used as bioinoculants to alleviate drought stress in wheat plants, in a sustainable manner. To the best of our knowledge, this is the first report of exploring the diversity and characterization of PGPR from the Kumaon Himalayas and their drought evaluation.